2019
DOI: 10.1111/dth.12988
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma Centrifugum Marginatum (KCM) after photodynamic therapy with good response to oral retinoids and topical 5‐fluorouracil

Abstract: Keratoacanthoma centrifugum marginatum (KCM) is a rare variant of keratoacanthoma (KA), characterized by progressive peripheral growth, and usually devoid of deep invasion. Different systemic (oral retinoids) or topical treatments have been reported, but there is not a well‐defined therapeutic protocol. We report the case of a KCM developing after photodynamic therapy (PDT) on the right leg of a 64‐year‐old woman. It was treated successfully with oral acitretin combined with topical 5‐Fluorouracil + salicylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several authors reported successful treatment with oral retinoids for KCM. In English‐based literature, to date, nine cases (including our patient) had good therapeutic response to retinoids, either etretinate, acitretin or isotretinoin, dose ranging from 0.5 to 1 mg/kg body weight 5,7‐12 . Our patient had a good and prompt response to acitretin.…”
Section: Discussionmentioning
confidence: 64%
“…Several authors reported successful treatment with oral retinoids for KCM. In English‐based literature, to date, nine cases (including our patient) had good therapeutic response to retinoids, either etretinate, acitretin or isotretinoin, dose ranging from 0.5 to 1 mg/kg body weight 5,7‐12 . Our patient had a good and prompt response to acitretin.…”
Section: Discussionmentioning
confidence: 64%
“…Solitary KCMs most commonly present on sunexposed surfaces of the head and neck as well as upper and lower extremities [4,[7][8][9][10]. The sizes of these lesions are variable, with some reports describing marginatum-type lesions as small as 5.0cm×5.0 cm to as large as 20.0cm×14.0cm [9,10].…”
Section: Case Discussionmentioning
confidence: 99%
“…While the cause is unclear, it has been found to be associated with ultraviolet ray exposure, smoking, and history of chemical exposure. In the recent years, cases that developed from photo dynamic therapy (PDT) have been reported (Silva, Estébanez, Martín, Monteagudo, & Montesinos, ). The lesions can be huge, with diameters as large as 20 cm.…”
Section: Discussionmentioning
confidence: 99%